2015
DOI: 10.1177/0310057x1504300105
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Level Interventions to Prevent the Acquisition of Resistant Gram-Negative Bacteria in Critically Ill Patients: A Systematic Review

Abstract: The rising incidence of multidrug-resistant Gram-negative bacterial (MDR-GNB) infections acquired in intensive care units has prompted a variety of patient-level infection control efforts. However, it is not known whether these measures are effective in reducing colonisation and infection. The purpose of this systematic review was to assess the efficacy of patientlevel interventions for the prevention of colonisation with MDR-GNB and whether these interventions are associated with a reduction in the rate of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It should be pointed out that the evaluation of the impact of antibiotics on in critically ill patients microbiota is highly complex because of the heterogeneity of dosing regimens, the co-administration of other antibiotics and other drugs that may also impact on its diversity. Therefore, to reduce the colonisation pressure, in addition to minimising exposure to antibiotics, it is essential to apply measures that have been shown to reduce colonisation from other patients or from colonised environmental surfaces; these measures include handwashing surveillance programs, adequate cleaning of patients, and the use of diverse strategies to minimise surface contamination [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…It should be pointed out that the evaluation of the impact of antibiotics on in critically ill patients microbiota is highly complex because of the heterogeneity of dosing regimens, the co-administration of other antibiotics and other drugs that may also impact on its diversity. Therefore, to reduce the colonisation pressure, in addition to minimising exposure to antibiotics, it is essential to apply measures that have been shown to reduce colonisation from other patients or from colonised environmental surfaces; these measures include handwashing surveillance programs, adequate cleaning of patients, and the use of diverse strategies to minimise surface contamination [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Small trials found benefits from probiotic colonisation by multidrug-resistant Gram-negative organisms in critically ill patients 16 and by vancomycin-resistant enterococci (VRE) in renal dialysis patients. 17 A Cochrane review 18 of probiotics to prevent acute upper respiratory tract infections (URTIs) included 13 RCTs, 10 of which were meta-analysed (including a total of 3720 participants).…”
Section: Existing Trials and The Research Gapmentioning
confidence: 99%
“…Meta-analysis indicates that probiotics can reduce antibiotic-associated diarrhoea (AAD), but more research is needed to determine which probiotics are associated with greatest efficacy and for which patients receiving which specific antibiotics 15. Probiotics may also reduce AMR colonisation,14 which could be important as most UTIs arise from autoinoculation with gut organisms.…”
Section: Introductionmentioning
confidence: 99%
“…They may prevent infection by blocking pathogenic colonisation and enhancing gut-immune interaction, with influence on mucosal and systemic immunity, leading to enhanced natural killer cell activity and vaccine response11 in older people 12 13. A systematic review and meta-analysis found that probiotics reduced the risk of upper respiratory tract infections (URTIs) and reduced antibiotic prescribing in adults and that side effects were minor 14. However, the review noted poor allocation concealment in several studies and heterogeneity in findings and recommended that future randomised controlled trials (RCTs) should ‘focus on older people’.…”
Section: Introductionmentioning
confidence: 99%